Insights into the secondary structures of lactam N-substituted stapled peptides. Issue 20 (13th May 2020) - Vasco, Aldrin V.; Moya, Celia G.; Gröger, Stefan; Brandt, Wolfgang; Balbach, Jochen; Pérez, Carlos S.; Wessjohann, Ludger A.; Rivera, Daniel G.
Abstract : NMR and CD studies together with molecular dynamics simulation reveal new insights into the s- cis /s- trans isomerism and the effect of the lactam bridge N -substituent on the secondary structure of stapled peptides. Abstract : Stapled peptides derived from the Ugi macrocyclization comprise a special class of cyclopeptides with an N -substituted lactam bridge cross-linking two amino acid side chains. Herein we report a comprehensive analysis of the structural factors influencing the secondary structure of these cyclic peptides in solution. Novel insights into the s- cis /s- trans isomerism and the effect of N -functionalization on the conformation are revealed.